Farm Mechanization and Farmers’ Preferences: Evidence from North Bank Plain Zone of Assam (Indian Journal of Extension Education, 2025)
The study was conducted during 2022 in the North Bank Plain Zone of Assam to assess the degree of farm mechanization, preferences toward farm machinery and farm operations, as well as factors influencing the extent of farm mechanization. Descriptive research design was followed and a purposive cum stratified random sampling technique was used for selection of 120 farmers as respondents for study. The degree of farm mechanization was recorded from medium to high for the majority of farmers, with an average farm mechanization area of 27.52 per cent. The majority of farmers showed a medium level of preference towards farm mechanization, but knapsack or power sprayer, portable milling machines, tractor-mounted thresher, tractor with rotavators or cultivator were the most preferred farm machineries. Irrigation, milling, plant protection, threshing, and land preparation were the most preferred farm operations for mechanization. Six socio-economic factors, viz. farm size, innovativeness, extension contact, credit availability, training exposures, and preferences for mechanization were positively and significantly contributed around 46 per cent variation of farm mechanization. Governments and non-government organizations should put efforts into promoting farm mechanization through the establishment of a custom hiring center for preferred farm machinery, easy access to government assistance, and strategic mobilization of resource-poor farmers.